MELIHAT KONSTRUKSI GENDER DALAM PROSES MODERNISASI DI YOGYAKARTA - Astuti, Dwi (Universitas Widya Mataram, 2020)
Like we know gender construction is always connected to cultural, and when the culture change it will effect gender construction. Yogyakarta lika other country in Indonesia,have high experience in modernisasi. This process will effect to culture in small or big part. This paper is a discription and explanation about gender construction in Yogyakarta on this era, written based on research. This research was conducted by necessity to know about the changes gender construction in community that have modernisation process. This process can create new relation between man and woman in many aspect. As a city that have strong patriarkhie culture, Yogyakarta can not avoid the modernisation process. And this process can influence that patriakhie culture, and than influence gender ralation indirectly in Yogyakarta. Gender construction in this paper is seen from four aspects, those are education, economi, politic dan double garden. Modernisation give effects on same aspek of gender construction. Although same aspect specially in public domain there is same changes in gender construction like in education, economi dan politic, but in domestic area specially doble garden, we can see that we find remains thd same. So we still can see the gender bias in domestic area. This research doing with discriptif method.